Positioning Control of an Antagonistic Pneumatic Muscle Actuated System using Feedforward Compensation with Cascaded Control Scheme - Y. Chan, C.; H. Chong, S.; L. Loh, S.; Alias, A.; Kasdirin, H. A. (International Journal of Integrated Engineering, 2020)
This paper presents a feedforward compensation with cascaded control scheme (FFC) for the positioning control of a vertical antagonistic based pneumatic muscle actuated (PMA) system. Owing to the inherent nonlinearities and time varying parameters exhibited by PMA, conventional fixed controllers unable to demonstrate high positioning performance. Hence, the feedforward compensation with cascaded control scheme is proposed whereby the scheme includes a PID controller coupled with nonlinear control elements. The proposed scheme has a simple control structure in addition to its straightforward design procedures. Though there are nonlinear control elements involved, these elements are derived from the open loop system responses that does not requires any accurate known parameters. Performance of the FFC scheme are then evaluated experimentally and compared to a PID controller with feedforward compensation (FF-PID) in point-to-point motion of different step heights. Overall, the experimental results show that the effectiveness of the proposed FFC scheme in reducing the steady state error to zero in comparison to FF-PID controller for all cases of step heights examined.